Estudio de la degradación de fenol sobre catalizador de arcilla pilarizada - Cardona-Castaño, Julio Andrés; Taborda-Ocampo, Gonzalo (Revista Científica, 2016)
The pillaring of a Colombian natural clay (bentonite) with the Al-Fe systems and the application for catalytic wet peroxide oxidation (CWPO) using phenol as target compound at 291,15 K has been studied. The solid was characterized by DRX and specific surface area using the BET model. The experiments were conducted at temperature of 291,15 K, atmospheric pressure, phenol concentration of 100 mg/L, catalyst concentration of 0,5 and 2,75 g/L and hydrogen peroxide concentration of 0,0265 and 0,053 M in semibatch and 7,4x10-3 and 0,0148 M in batch, equivalent to 50 and 100% of the stoichiometric amount needed for complete phenol degradation, respectively.Both processes were compared in terms of degradation of phenol, degradation of H2O2 and aromatic intermediates and short chain acids. It was determined that the rate of degradation of phenol and aromatic intermediates is slower in the semibatch process. However, more efficient hydrogen peroxide in the semibatch process was presented use favoring reaction with organic species and reducing competitive reactions.